An Introduction to Propensity Score Analysis: Checklist for Clinical Researches - Totik, Nazlı; Yücel Karakaya, Sevinç Püren; Alparslan, Zeliha Nazan (European Journal of Therapeutics, 2023)
Background: Propensity score analysis is a widely used method to estimate treatment effect in dealing with the selection bias (i.e. lack of randomization) of observational studies. Although, there are relatively many guidelines in the literature for the adoption of this analysis, no checklists exist. Objective: In this study, we propose a basic guideline for propensity score analysis, a tutorial that may be used to improve the quality of studies which implement this analysis. Additionally, in line with this guideline, we present an easy-to-use checklist which will assist researchers in the analysis process. Conclusion: In light of the principles in this guideline/checklist, we propose that minor updates be considered for STROBE.